ADOLESCENT’S EXPRESSIONS ABOUT ILLICIT DRUG USE - Murillo Castro, Ligia (2013)
The research described below, with qualitative methodology, through the technique of two focuses groups, was conducted in two non-governmental organizations (NGOs) in Costa Rica. This analysis revealed the experiences of young women and men during the process of consumption of illicit drugs. In light of his stories, it is bare issues of personal expe-riences with regard to family relations, their friends, their communities, and educative spaces.